Expression and Prognostic Significance of PDIA3 in Cervical Cancer. (11th November 2022) - Zhang, Jing; Li, Hui; Li, Huling; Lin, Dandan; Wang, Xiaoyan; Wang, Kai
Abstract : To investigate the expression of protein disulfide isomerase A3 (PDIA3/ERP57) in cervical cancer and its clinical prognostic significance as well as its function and possible action mechanism in the progression of cervical cancer. Based on TIMER2.0 database, the human protein map (Human Protein Atlas) was used to determine the expression level of PDIA3 protein for the analysis of PDIA3 expression in 39 The Cancer Genome Atlas (TCGA) tumors. The PDIA3 expression in cervical cancer tissues in the TCGA and Genotype-Tissue Expression databases was further verified based on the GEPIA2 database to analyze the relationship between the PDIA3 expression and the pathological stage of cervical cancer patients. Immunohistochemistry was used to detect the PDIA3 expression in cervical cancer tissue microarray, including 111 cancer tissue samples and 24 adjacent cancer tissue samples, and the relationship between PDIA3 protein expression and clinical characteristics of patients with cervical cancer was analyzed. The Kaplan–Meier method and log-rank test were used for survival analysis. Based on the cBioPortal database, the Spearman's and Pearson's methods were used to analyze the correlation between PDIA3 expression and DNA methylation. The correlation between PDIA3 expression and the infiltration levels of each immune cell in cervical cancer was evaluated. The STRING was used to construct protein interaction network. Based on LinkedOmics database, the Spearman's method was used to analyze the co-expressed genes of PDIA3 in TCGA cervical cancer. The gene ontology functional enrichment analysis was performed on Top 50 differentially co-expressed genes based on DAVID database. The PDIA3 expression in cervical cancer tissues was significantly higher than that in normal tissues, which (F = 2.74, PR (> F ) = 0.0436) was significantly increased with the progression of tumor stage, and PDIA3 showed strong immunoreactivity in cervical cancer tissues. In cervical cancer patients, overall survival (P = 0.014 ), disease-specific survival (P = 0.013 ), disease-free interval (P = 0.023 ), and progression-free interval (P = 0.001 ) in those with high expression of PDIA3 were significantly lower than those with low expression, suggesting that high expression of PDIA3 was associated with poor prognosis. In cervical cancer, high expression of PDIA3 was associated with DNA methylation and negatively correlated with B cell memory (r = − 0.132, P = 0.021 ), T cell regulatory (r = − 0.127, P = 0.026 ), monocytes (r = − 0.204, P = 0 ), and macrophages M2 (r = − 0.142, P = 0.013 ), whereas positively correlated with levels of NK cell activated (r = 0.162, P = 0.005 ) and mast cells activated (r = 0.119, P = 0.037 ). The genes positively correlated with PDIA3 expression included HSPA5 and PPIB, which were mainly enriched in biological processes, such as endoplasmic reticulum (ER) protein folding and ER stress response. PDIA3 can be used as a marker of poor prognosis of cervical cancer. The expression level of PDIA3 is closely related to the survival and prognosis of cervical cancer patients, DNA methylation, and immune cell infiltration.